The Economic Feasibility of the beekeeping project Using the method of mobile promiscuous - عبد, حميد عبيد; جبر, مأمون احمد; عويد, عايدة نعمة (Journal of Economics and Administrative Sciences, 2012)
An update of our research is the first to develop and reform the agricultural sector . and promoting production and productivity of this sector multi-sources , which is the management and beekeeping one source . Been applied to the style of beekeeping mobile promiscuous includes twentieth cell in the Iraqe project of mussiab . in which there exist a variety of crops and trees . Experiment had proved successful and led to raise the level of npoduction of single Dell of the honey to 49 kg over the previous year and surpassed the average production percell in the province of Babylon , which the amount of 13.945 kg , another quantity of honey has been abtained by feeding different groups of bees . as well as propols and royal jelly and parcels Rate of return of about 9.58 perdinar and return on invested capital of about 8.52 . in addition to the design of aprivate vechicle to help the farmer on the process of movement , are promiscuous mobile at all time and is independent of other establiched .